Penelitian-Penelitian Tentang Timbulan Limbah B3 Medis dan Rumah Tangga Selama Bencana Pandemic Covid-19 - Prihartanto Prihartanto (Jurnal ALAMI : Jurnal Teknologi Reduksi Risiko Bencana, 2020)
Abstract The generation of medical and municipal waste during the COVID-19 pandemic has the potential to become a medium for spreading the virus if it is not handled properly. The lack of information regarding the generation of medical and the effectiveness of handling infectious waste is one of the factors that influence the handling of Covid-19 hazardous waste. In this study, a literature review will be presented regarding several studies on the generation of Covid-19 medical hazardous waste that have been carried out in several developing and developed countries from December 2019 to mid-2020. In addition, a comparison of the handling of infectious municipal waste in developing and developed countries will be presented in this paper during a pandemic. It is hoped that this research can be used as a reference for further research on the generation of hazardous medical waste and handling municipal-scale infectious waste due to the Covid-19 pandemic. Keywords: Covid-19, hazardous waste, waste generation, medical waste, municipal waste Abstrak Timbulan limbah medis dan rumah tangga pada masa pandemi COVID-19, berpotensi menjadi media penyebaran virus bila tidak ditangani dengan benar. Minimnya infomasi mengenai timbulan limbah medis dan efektivitas penanganan limbah infeksius menjadi salah satu faktor yang berpengaruh terhadap penanganan limbah B3 Covid-19 ini. Dalam kajian ini akan disampaikan tinjauan pustaka mengenai beberapa penelitian tentang timbulan limbah medis B3 Covid-19 yang pernah dilakukan dibeberapa negara berkembang dan negara maju sejak Desember 2019 hingga pertengahan 2020. Disamping itu dalam makalah ini akan dipaparkan perbandingan penanganan limbah infeksius rumah tangga di negara berkembang dan negara maju selama terjadi pandemik. Diharapkan penelitian ini dapat digunakan sebagai salah satu rujukan bagi penelitian lanjutan tentang timbulan limbah medis B3 serta penanganan limbah infeksius skala rumah tangga akibat pandemik Covid-19. Kata kunci: Covid-19, limbah beracun dan berbahaya, timbulan limbah, limbah medis, limbah rumah tangga